Physical activity interventions for post-stroke cognitive recovery: a systematic review and network meta-analysis of comparative effects - Wang, Hongyu; Li, Dong; Li, Shuang; Zhang, Xiaolin; Zang, Wanli; Zhu, Ying; Zhang, Shixuan; Xu, Feng; Xiao, Zixian; Guo, Kelei (Frontiers in Neurology, 2025)
BackgroundPost-stroke cognitive dysfunction imposes significant burdens on individuals and healthcare systems. Although physical activity are increasingly recognized as adjunct therapies for cognitive rehabilitation, uncertainties persist regarding their comparative effectiveness. The current evidence lacks direct or indirect comparisons of physical activity programs. This study systematically evaluated the effectiveness of intervention measures through network meta-analysis, providing reference measures for cognitive function recovery in stroke populations.MethodsWe systematically searched PubMed, Cochrane Library, Embase, and Web of Science from their inception through August 2024 to identify randomized controlled trials investigating the effects of physical activity interventions on cognitive function in stroke patients. Two independent reviewers conducted literature screening, data extraction, and quality assessment. Network meta-analysis was performed using Stata 15.1.ResultsA total of 26 randomized controlled trials involving 1,408 participants were included in the analysis. The findings revealed that compared with routine medical care, multi-modal exercise significantly improved cognitive function (SMD = −5.58, 95% CI: −8.00 to −3.16), followed by aerobic exercise (SMD = −4.22, 95% CI: −7.04 to −1.41). The surface under the cumulative ranking curve (SUCRA) probabilities for the eight intervention types were as follows: multi-modal exercise (96.7%), aerobic exercise (80.9%), etc.ConclusionOur study indicates that multi-modal exercise (e.g., combined programs integrating strength training, balance exercises, and aerobic training such as running and cycling) and high-intensity aerobic exercise show superior efficacy in enhancing cognitive recovery among stroke patients. Furthermore, while physical activity is proven to be beneficial, the major challenge remains in developing effective strategies to promote long-term adherence to regular physical activity routines.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024579294.